Success Model for Audit Business Operators in the Thai Capital Market - Kamolchannokkul, Boonlert; Kothana, Thanaphon; Phangnirand, Bundit (The Journal of Development Administration Research, 2025)
This research aims to: 1) study the level of success of audit firms in the Thai capital market, including technology adoption, management, management innovation, and service quality; 2) study the influence of technology adoption, management, management innovation, and service quality on the success of audit firms in the Thai capital market; and 3) create a model of success for audit firms in the Thai capital market. This research utilizes a mixed-method approach, combining quantitative and qualitative methods. The quantitative research sample consisted of 420 audit firms in the Thai capital market. The sample size was determined using a 20-fold criterion, multi-stage random sampling, and quota sampling. Questionnaires were used for data collection and analysis using structural equation modeling. For the qualitative research, in-depth interviews were conducted with 15 officials from the Securities and Exchange Commission, the president of the Association of Auditing Firms, and representatives of accounting firms in the capital market. Content analysis was used to analyze the data. The results showed that: 1) innovation, the success of audit firms in the Thai capital market, service quality, organizational management, and technology adoption were at the highest levels; 2) technology adoption and service quality were at the highest levels. Management and management innovation have a statistically significant effect on the success of auditing operators in the Thai capital market at the .001 level. 3) The success model of auditing operators in the Thai capital market that was developed is the T2SMI Model” (T=Technology acceptance: , S=Service quality, M=Management administration I= Innovation management in the middle S=Success) is a model for agencies that support and promote the success of auditing operators in the Thai capital market that focuses on finance, stakeholder satisfaction, internal management processes, and learning and growth.